Pension Reform, Private Saving, and the Current Account in a Small Open Economy - Schimmelpfennig, Axel (IMF Working Papers; Working Paper ;, 2000)
The macroeconomic implications of a pension reform that substitutes a high-return fully-funded system for a low-return pay-as-you-go system are discussed in an overlapping generations, neoclassical growth model. With forward-looking individuals, a debt-financed reform worsens the current account, while a tax-financed reform leaves the current account unchanged. With myopic individuals, a debt-financed reform leaves the current account unchanged, while a tax-financed reform improves the current account. Hence, tax-financing, which is equivalent to pre-funding, should be the preferred reform strategy in a small open economy with a weak current account position.